Completion report: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - International Food Policy Research Institute; Southeast Asian Regional Center for Graduate Study and Research in Agriculture (International Food Policy Research Institute, 2025)
The ATMI-ASEAN project was launched on October 7–8, 2016, in the Philippines. It is a five-year project funded by International Funds for Agriculture Development (IFAD) with a year’s extension due to the Coronavirus disease 2019 (COVID-19) pandemic. The implementation of the project was led by the International Food Policy Research Institute (IFPRI) and co-implemented by the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA). The ATMI-ASEAN project comprises three main components: Component 1. Policy studies and expert workshops; Component 2. High-level policy forums (HLPFs) and roundtables; and Component 3. Technical assistance for planning and policy development. Each component was scheduled and implemented over the project implementation from 2016 to 2021, then extended for a year to finalize the project implementation affected by the COVID-19 pandemic. This report elaborates on all project outputs throughout the implementation.